Family fortresses in Zika Congenital Syndrome according to Betty Neuman - Laís Helena de Souza Soares Lima; Estela Maria Leite Meirelles Monteiro; Maria Wanderleya de Lavor Coriolano; Francisca Márcia Pereira Linhares; Ana Márcia Tenório de Souza Cavalcanti
ABSTRACT Objectives: to identify elements that contribute to strengthen the family system of children with Zika virus congenital syndrome according to Betty Neuman's theory. Methods: qualitative research, carried out in the outpatient service of a public hospital in the city of Recife, Brazil, with 13 mothers, by semi-structured interviews. The IRAMUTEQ software was used for data analysis and the interpretation was carried out according to Betty Neuman's Systems Model Theory. Results: the dendrogram originated five categories, which we named: Family Routine, Health Service Assistance, Changes in Lifestyle, Support Network, and Social Repercussions of Care for the the Family Context. Final considerations: nursing actions based on Betty Neuman's theory provide subsidies for the recognition of elements that strengthen the defense lines of the family system. These resources can be explored, aiming to maintaining the well-being and balance in the context of the family system.